Unilateral carrageenan injection into muscle or joint induces chronic bilateral hyperalgesia in rats - Radhakrishnan, Rajan (2003)
Chronic musculoskeletal pain is a major clinical problem and there is a general lack of animal models to study this condition. Carrageenan is commonly used to produce short-lasting acute inflammation and hyperalgesia in animal models. However, the potential of carrageenan to produce chronic, long-lasting hyperalgesia has not been evaluated. In the present study, we investigated the long-term effects of carrageenan injected into joint or muscle in rats. Rats were injected with 0.3, 1 or 3% carrageenan in one knee joint or gastrocnemius muscle and hyperalgesia to mechanical (measured as decreased withdrawal threshold) and heat (measured as decreased withdrawal latency) stimuli of both paws assessed before and at varying times after injection, through 8 weeks. Histological changes were examined only after injection of 3% carrageenan. Three percent carrageenan injected in the muscle or knee produced hyperalgesia to mechanical and heat stimuli ipsilaterally, which lasted 7–8 weeks and spread to the contralateral side 1–2 weeks after injection. One percent carrageenan injected to the knee joint or gastrocnemius muscle, produced hyperalgesia that was shorter-lasting and remained ipsilateral; 0.3% carrageenan injected into the knee joint or gastrocnemius muscle had no effect. Three percent carrageenan injected into the skin surrounding the knee joint did not produce hyperalgesia. A similar pattern of inflammatory changes was observed histologically for both the joint and muscle tissues. Acute inflammation was observed for the first 24 h with edema and neutrophilic infiltration evident as early as 4 h. At 1 week, the inflammation converted to primarily a macrophage response with scattered mast cells. The data suggest that animals injected with 1 or 3% carrageenan in the knee joint or gastrocnemius muscle could be used as models of acute inflammation through 24 h and chronic inflammation after 1 week. Furthermore, 3% carrageenan injected into deep tissues produces hyperalgesia that spreads to the contralateral side, at the same time period as the inflammation transforms from acute to chronic.